Labeling Thoughts - Geller, M. J. (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2023)
A discussion of Visualizing the Invisible with the Human Body, Physiognomy and Ekphrasis in the Ancient World, edited by J. Cale Johnson and Alessandro Stavru, that focuses on what common ground the numerous ancient cultures that the book encompasses share and on how this bears on the study of Mesopotamian culture.